ПРИСТРІЙ ДЛЯ КОРИГУВАННЯ ФОРМИ НАПРУГИ МЕРЕЖІ, ЯКА ЖИВИТЬ ПОТУЖНИЙ КЕРОВАНИЙ ВИПРЯМЛЯЧ - Чиженко, О.І.; Блінов, І.В. (Інститут електродинаміки Національної академії наук України, 2022)
A circuit solution of a device for correcting the waveform of the mains voltage, which feeds a controlled semiconductor rectifier of comparable power, is proposed. The sags and swells in the mains phase voltage, which occur during current switching from one phase to another, are compensated by correction pulses, which are transformed into these phases from the phase, which is not involved in switching, using transformers. The mains phase voltage correction circuit, which generates the correction pulses, is connected to the rectifier by four groups of gates in each phase. These groups contain two counter-parallel controlled thyristors, which connect the rectifier to the network phases and its neutral conductor. An algorithm for controlling the controlled thyristors is described. Ref. 8, fig. 2.